The Rise and Tide of the Minangkabau Traditional Trading in Kuala Lumpur: A Preliminary Research - Sismudjito Sismudjito; Rizabuana Ismail; Darul Amin Abdul Munaf (Faculty of Geography, Universitas Gadjah Mada, 2015)
This article is discussing on how the rise and tide of Minangkabau traditional trading occur in Kuala Lumpur. The research focused on four areas in Kuala Lumpur, Chow Kit, Kampung Baru, Kampung Dato’ Keramat and Mesjid India area, reveals that there are some small stalls of Minangkabau traditional trading are now owned by another Indonesian ethnicity such as Acehenese and Boyanese tribe. Meanwhile, some of the businesses are still possessed by Minangkabau tribe such as Nasi Padang and textile trading. The phenomenon is affected by the lack of business innovation, capital, local competitor and the fact that they are unable to follow the trend in business. Even though, there are some of well-developed traditional business run by Minangkabau people in Kuala Lumpur due to the existence of marketing creativity, innovative items, and the conducive partnership with another Minangkabau entrepreneurs in the textile merchant in form of kiosk or arcade in Mesjid India area that has connection with another counterpart of the nationwide including Sabah and Sarawak.